Perancangan Sendi Lutut Prostetik untuk Penderita Amputasi Transfemoral di Indonesia - Marihot Nainggolan; Hanky Fransiscus; Daniella Alexandra Djulaini (Jurnal Rekayasa Sistem Industri, 2023)
The main problem that experienced by transfemoral amputees in Indonesia is limited mobility, so they need prosthetic limbs to walk and do daily activities. However, the limited movement and also expensive price of the prosthetic knee joint causes not all the needs of the transfemoral amputee can be accommodated. This study aims to design the artificial leg joints that can meet the needs of the Indonesian amputees. Stages of this research include searching for unmet user needs, developing concepts to produce a prosthetic knee joint repair plan and evaluating it. From this research, six initial concepts of prosthetic knee joints, and one concept (AD+) has been selected using concept screening and concept scoring. A physical prototype has been made using printer 3D. The final prosthetic knee joint using polycentric knee type joint with constant friction drive type, having a human knee joint shape, has a height dimension of 188.84 millimeters and width of 82.46 millimeters, has a maximum bending angle of 151.4O, mass 598, 62 grams, can support a maximum load of 272 kilograms (according to CAD model), made of nylon, has a production cost about one million rupiah (less than USD100), has a single speed and impact high level ambulation, and has a rotator and lock function. Evaluation is done by simulation and qualitative assessment. The results showed that 68.42% of the needs were met well and 31.58% were adequately met by this new proposed prosthetic knee joint design.